Hierarchical Patterns: Harnessing Localized Ridges for High‐Aspect‐Ratio Hierarchical Patterns with Dynamic Tunability and Multifunctionality (Adv. Mater. 11/2014). (March 2014) - Cao, Changyong; Chan, Hon Fai; Zang, Jianfeng; Leong, Kam W.; Zhao, Xuanhe
<x xml:space="preserve">Abstract</x> A simple yet effective method, described on page 1763 by X. Zhao and co‐workers, to generate high‐aspect‐ratio, hierarchical, and dynamically tunable topographical patterns over large areas by harnessing the localized‐ridge instability in nanofilms. The new patterns have led to extraordinary functions, including extremely stretchable super‐hydrophobic coatings and biomimetic cell‐culture substrates capable of controlled stem‐cell alignment on demand. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>